PERAN ORANG TUA DALAM MENGENALKAN IT PADA ANAK KELAS 1 MI MA’ARIF BOWONGSO KECAMATAN KALIWIRO KABUPATEN WONOSOBO - Mulyani, Pamungkas Stiya (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Parents? roles in introducing IT to children of grade 1 MI Ma?arif Bowongso in Kaliwiro district Wonosobo regency are veryimportant as, along with the advance of science and technology, the children are expected to have ability in IT so that theyare able to know, recognize, and at least operate computer well. A research has been conducted to figure out parents? roles inintroducing IT to children. The approach used was qualitative method with descriptive design and data collection techniquein the form of interview as well as documentation. The data was analyzed by using the technique of data reduction, datapresentation and data verification. The research result shows that parents? roles in introducing IT to children of grade 1 MIMa?arif Bowongso in Kaliwiro district Wonosobo regency have not been maximum as there are many children that still cannotoperate computer. It is the result of the lack of parents? knowledge and understanding in introducing and operating IT media.From the research result, it can be concluded that The research result shows that parents? roles in introducing IT to children ofgrade 1 MI Ma?arif Bowongso in Kaliwiro district Wonosobo regency have not been maximum.